Protocolo "watch and wait" para pacientes com adenocarcinoma de reto no Hospital de Clínicas - UNICAMP - Mukai, Natalia Sayuri, 1986- (2019)
Orientadores: Carlos Augusto Real Martinez, Claudio Saddy Rodrigues Coy